Late Neoarchean magmatic and subsequent metamorphic events in the northern North China Craton: SHRIMP zircon dating and Hf isotopes of Archean rocks from Yunmengshan Geopark, Miyun, Beijing - Shi, Y.; Wilde, Simon; Zhao, X.; Ma, Y.; Du, L.; Liu, D. (Elsevier Science BV, 2012)
The Miyun Geopark is located in the northern part of the North China Craton and includes a variety of Archean granitoids and metamorphic rocks. SHRIMP zircon dating documents their emplacement ages at 2567–2508 Ma, metamorphic events at ca. 2.50 Ga, 2.44 Ga, and 1.82 Ga. Late Neoarchean basement rocks elsewhere in the North China Craton document a similar evolutionary history with intrusion of granitoid rocks commencing at ca. 2590 Ma and reaching three peaks at about 2550, 2520, and 2500 Ma; these rocks then underwent regional metamorphisms at ca. 2.50 Ga, 2.44 Ga, 1.92 Ga, and 1.82 Ga. Positive εHf(t) values of + 1.7 to + 7.6, with model ages younger than 3.0 Ga, for magmatic zircons from these late Neoarchean intrusive rocks indicate that they are predominantly derived from juvenile crustal sources and suggest that significant crustal growth occurred in the northern North China Craton during the Neoarchean. The intrusive rocks in the Miyun area are part of an extensive province of late Neoarchean magmatism and appear to be related to mantle plume activity at this time.